Peran Guru Ilmu Pengetahuan Sosial Dalam Mengatasi Perilaku Bullying Pada Siswa SMP Kristen Getsemani Manado (Lembaga Pengembangan Kinerja Dosen, 2025)
The research problem is formulated as follows: What is the role of social studies teachers in eliminating bullying behavior among students at Getsemani Christian Junior High School in Manado? The purpose of this study is to determine the role of social studies teachers in eliminating bullying behavior at Getsemani Christian Junior High School in Manado. The research method is qualitative, with data collection techniques including observation, documentation, and interviews. The informants are Social Studies teachers and five students, with qualitative analysis conducted according to Miles and Hubberman. The research results indicate: 1) Bullying behavior among students at SMP Kristen Getsemani Manado, including: a) Verbal abuse, b) Insults, c) Threats, d) Humiliation, e) Mockery, f) Gossip, and g) Humiliating jokes. 2) Factors contributing to bullying behavior at SMP Kristen Getsemani, including: a) Lack of character education, b) Lack of parental supervision, c) Lack of school supervision, d) Lack of consequences, e) Influence of social media, and f) Social pressure. 3) Efforts by teachers to eliminate bullying behavior among students at SMP Kristen Getsemani Manado, through the following methods: 1) Providing guidance, 2) Conducting anti-bullying campaigns, 3) Motivating victims, 4) Involving parents, 5) Teaching character education, and 6) Setting an example or providing role models.